Improving the Quality of Education Through Infrastructur in Era 5.0 - Yusutria; Annur Fajri; Egi Nur Hudatun; Febriana, Rina Febriana (Universitas Kristen Satya Wacana, 2024)
The research aims to explore improving the quality of education through infrastructure in the 5.0 era. Preparing educational facilities and infrastructure is critical to maintaining them properly and appropriately, especially in this 5.0 era. All school officials must maintain facilities and infrastructure well, including principals, teaching staff, and students. If educational facilities and infrastructure in schools are maintained properly and correctly, of course, the impact will be on the quality of education. This research used a qualitative descriptive method by explaining what underlies the results obtained by compiling the data or information the researcher has collected with the final results in written form. Data collection techniques are done through interviews, observation, and documentation. The research results show that the efforts made by schools are to improve the quality of education through 5.0-era infrastructure. Namely by doing: 1). Planning educational facilities and infrastructure through needs analysis by analyzing the financing that must be covered, adjusting the quality of facilities and infrastructure, 2). Inventory, 3). Settings, 4). Maintenance, 5). Removal through the deletion procedure. 6) Providing training to educators and education staff in using existing facilities so that they are maintained and function as they should.